The Texas Legation papers, 1836-1845 - Stevens, Kenneth R., 1946-; Texas Christian University. Center for Texas Studies; TCU Press (Fort Worth, Tex. : TCU Press, 2012)
The papers of the Republic of Texas between independence and statehood.
"A joint project of The Center for Texas Studies at TCU and TCU Press."
Includes bibliographical references and index.
Keywords: Texas. -- Legation (U.S.) -- Sources; Diplomatic and consular service -- Texas -- History -- Sources; Statesmen -- Texas -- Correspondence; Texas -- History -- Republic, 1836-1846 -- Sources; Texas -- Foreign relations -- United States -- Sources; United States -- Foreign relations -- Texas -- Sources